Pengaruh Faktor Iklim Terhadap Kejadian Demam Berdarah (DBD) di Jakarta Pusat Tahun 2014-2023 - Nemi Muhaeminah; Ririn Arminsih Wulandari (Jurnal Penelitian Sains dan Kesehatan Avicenna, 2026)
World Health Organization (WHO) documented a ten-fold surge in reported cases worldwide increasing from 500 000 to 5.2 million. In Indonesia, the increase from 2018 to 2022 includes 440 cases (85,6%) in 2018, rising to 484 cases in 2022. Meanwhile, in Central Jakarta there has been an increase in cases, in 2018 they’re 112 case increase 752 Dengue Fever cases in 2022. Purpose: This study aims to analyze the impact climatic factors (air temperature, humidity, rainfall, and wind direction) on dengue fever cases in Central Jakarta. Methods: This research method uses a time-trend ecological study design with the inclusion criteria of cities that have weather monitoring stations from the Climatology and Geophysics Meteorology Agency. Results: The climatic factors that influence of Dengue Fever in Central Jakarta from Januari 2014 to December 2023 are as follows : humadity with p value 0,02<0,05 has positive correlation coefficient (r=0,210). The duration of sunlight has a weak negative correlation with DF incidence (r= -0,185) ad shows a significant with p value 0,044. In contrast, the temperature variable has a very weak positive correlation with DF incidence (r=0,003) and is not signification related (p=0,977). Rainfall has a weak positive correlation with DF incidence (r=0,141) and is not significant (p=0,123). Wind direction shows a weak positive correlation (r=0,126) and is not significant (p=0,170). Wind speed has a very weak negative correlation (r= -0,089) and is not significantly related p=0,336. Conclusion: The increase in population is accompanied by an increase in dengue cases. Climatic factors in this case humidity, rainfall, and wind direction have a significant effect on the incidence of DHF.